GERAKAN POLITIK PENEGAKAN SYARI’AT ISLAM DI ERA REFORMASI KASUS MAJELIS MUJAHIDIN INDONESIA 2000-2005 - Aziz, Abdul (Jurnal Review Politik, 2012)
Since the end of colonialism in Muslim countries, the political system of nation states can integrate the entire of community, including in Indonesia. Based on the background, this article will answer the question of whether that separates between religious authorities on the one hand, and the political authorities on the other. Political Islam, in particular of the Islamic political movement, trying to unify these two authorities. Mujahideen Movement is one of them. This is an attempt to defend "the interests of Islam" from political marginalization, and various social imbalance, which is thought to occur due to the poor ability of the state to solve community problems. The phenomenon of the movement of Islamic law (Shari'a) which is enforced by MMI Indonesia, known as the Islamic political movement.